Paraguay’s Path Toward the Simplification of Procedures in the Approval of GE Crops - Benítez Candia, Nidia; Fernández Ríos, Danilo; Vicién, Carmen (Frontiers in Bioengineering and Biotechnology, 2020)
Agricultural biotechnology was first regulated in Paraguay in 1997. As part of this process, in November 2012, the Paraguayan Ministry of Agriculture joined the Partnership for Biosafety Risk Assessment and Regulation, led by ILSI Research Foundation. The purpose of the program was the development of capacity building activities and as a result the regulatory authorities in Paraguay incorporated the problem formulation approach to environmental risk assessment into their regulatory processes, leading directly to improved efficiency, with more timely decisions. Shifting to a problem formulation-based decision-making system was not simple, since practice and experience is always required to make professional risk assessors. Despite the continuity of approvals, there was a lag in the response time reflected in the number of events approved. During 2019, a simplified approval procedure for events that have been assessed by sound and experienced regulatory systems was introduced. Acceptance of third-country assessments can allow regulatory systems to make better use of their human, financial, and institutional resources, and stimulate inter-agency cooperation. In this work we aim to present the recent evolution of the regulatory system in Paraguay towards the establishment of a simplified procedure for GE crops that have been already assessed by sound and experienced regulatory systems, taking into account several scientific criteria. This requires the commitment of governments to support stability of the institutions responsible for the regulatory implementation, and also encourages countries to put work into the preparation and publication of decision documents, which are the basis for the commercialization of GE events.